Language as a Socio-Cultural Semiotic: A Case Study on the Fiction Text - Latjuba, Ade Yolanda (Lingua Cultura, 2016)
This article was intended to prove that a language could reflect a socio-cultural situation at a certain period of a nation. The first step taken to achieve this end was choosing a text that had the appropriate register, in accordance with the purpose. The fictional text â€œNocturneâ€ was a register which was chosen as the object of research to prove that the language might reflect the socio-cultural situation of a particular period of a nation. This register had the potential of meaning, both visible and hidden. Meaning that appeared to come from the system of meaning that was owned by choice of words, phrases, and sentences. While the meaning that was not visible is the potential meaning that indirectly was stated in the text. The method of this article was interpreted by using a semiotic approach. These words were then associated with sentences in the text, which explained series of event or actions of the storyâ€™s figure. From here, it obtained the actual meaning of the text in question. And this article finds that the form of signs that potentially could have a meaning that is integrated into the text. Thus, by isolating the socio-cultural system that has the meaning potential in the text, the marker can easily be interpreted through the semiotic approach. The overall theme of the story can be interpreted two-fold: an overview of the concept of culture Bugis-Makassar Siriâ€™ or impression of the situation calm.